RACISM ISSUE IN JERICHO BROWN'S SELECTED POEMS - Ramli Ramli (Universitas Muhammadiyah Gorontalo, 2021)
The purpose of this research was to find out the racial issues that were contained in the poem and to find out the impact of racism on black people in the poem. The method used was descriptive method with a social approach. The researcher really understands the contents of the poem by reading it repeatedly, noting important parts, then compiling data that are directly related to this research. The results showed that in Jericho Brown's poetry, there were many issues of racism that occurred both from the past and the present. There were racism types that can be found in the poem, such as discrimination, injustice, skin color, segregation and slavery and in this poem, it is also found that there are racist acts against black people in the form of oppression, death, hunger, and death that happened to people. black skinned. In this study, it is explained that racist acts have a bad impact on those who experience them and there are many types of racist acts that can be understood. The conclusion of this research was various types of racist acts are found in three of Jericho Brown's poems entitled the tradition, at the end of hell, and langstone blue, namely discrimination actions, injustice, segregation, slavery and skin color by people with white skin against black people in the past and present.